Pengaruh Kompetensi Kepribadian dan Motivasi Kerja terhadap Kinerja Guru SMA Negeri 8 Medan - Andani, Merry; Tumanggor, Rytauli; Zainuddin, Zainuddin; Sinaga, Anton (JURNAL PROINTEGRITA, 2020)
ABSTRACT Performance is the work quality and quantity achieved by a person in carrying out his duties in accordance with the responsibilities given to him. Some elements that are often used in assessing teacher performance are mastery of subject matter, ability to manage classes and the ability of teachers to increase student learning interest. This study aims at determining the effect of personality competency and work motivation partially and simultaneously on performance of teachers in SMA Negeri 8 Medan. The population in this study is all teachers who taught at SMA Negeri 8 Medan, with a total of 41 teachers. The entire population of 41 people was taken as a sample. Data collection techniques in this study are questionnaires, interviews and documentation studies. While the data analysis technique used is the classic assumption test, multiple regression, t test, F test and coefficient of determination. The results show partially the personality competency of teachers had a positive and significant effect on the teacher performance of SMA Negeri 8 Medan. The better the teacher's personal competence, the better the teacher's performance will be. Partially the work motivation of the teacher has a positive and significant effect on the teacher performance of SMA Negeri 8 Medan. The higher the teacher's work motivation, the better the teacher's performance will be. Simultaneously personality competency and work motivation of teachers have a significant effect on teacher performance in SMA Negeri 8 Medan The coefficient of determination shows that 90,20% variation in teacher performance can be explained by personality competency and teacher's work motivation simultaneously, while the remaining 9.80% is explained by other factors, such as education and work discipline